Scientific research, practice and experience: a reflection about preschool teacher training (2021)
This article aims at building some reflections framed by the scientific knowledge, and the authors’ pedagogical experiences along all the years they had trained pre-service preschool teachers. The first element that will be presented is linked to the students’ reflections about their professional choice. Thus, the students’ self-evaluation is understood as a continuous strategy to recognize their practice (know how to do), experience (know how to be) and pedagogical knowledge, that the students construct based on theory to support their teaching practice (know how to know). The second element that will be presented is linked to reflections upon the relationship between pre-service practice and formative research. Those should be part of preschool teachers’ practice since they offer a unique possibility to reach meaningful transformations in children’s educational contexts. Finally, we suggest some forward planning related to what should be considered in the field of pre-service training in order to address emerging and changing situations that concern Colombian children. We consider that it is necessary to get ready for those situations not from an idealist point of view, but rather real situations trigger discussions, inquiries and confrontations that start reflection processes.